Attitudes towards the new genetic and assisted reproductive technologies in Sri Lanka: A preliminary report - Dissanayake, V.H.W.; Simpson, R.; Jayasekara, R.W. (Taylor & Francis, 2002)
ABSTRACT Discussions about the ethical and social impacts of the new reproductive and genetic technologies have tended to be dominated by concerns that have originated in European and North American societies. In this paper, we explore perspectives on these issues from a distinctively Asian perspective. Using a questionnaire-based descriptive study, we examined the attitudes of 36 Sri Lankan Medical Of®cers following a course preparing them for the Master of Surgery (Obstetrics and Gynaecology) Part I examination in Colombo. The survey highlights an extremely positive response to many aspects of the new technologies in contrast to the long-standing ambivalence towards prenatal diagnosis and the prospect of therapeutic termin- ation. We end by discussing some of the ways in which ideas about re-birth and fate may in¯ uence the reception of the new technologies among some doctors